Kehidupan Anak Jalanan Pada Total Institution UPTD Kampung Anak Negeri - Anggraeni, Della Puspita; M.Si., Dr. Sugeng Harianto (Paradigma, 2023)
The empowerment of street children in Surabaya through the Surabaya City Social Service has created an institution for sheltering socially disadvantaged children, namely UPTD Kampung Anak Negeri. Street children are fostered to increase their potential and change their self-image to become normative and independent. Discussing life behind UPTD Kampung Anak Negeri, there is behavior determined by the institution. Street children recognize the institution and show actions in accordance with and against its rules. This research uses a qualitative approach with the perspective of Erving Goffman’s Total Institution Theory to analyze the data. The results showed that UPTD Kampung Anak Negeri has a big influence on fostered children. Unharmonious family factors trigger the entry of children into this institution. In it, strict social control is created through rules and punishments, shaping children’s behavior. Their identity is transformed into "inmates," leading to a loss of autonomy and stigmatization. Interpersonal conflicts between staff create social tension, and children’s behavior is influenced by social control, strict schedules, and CCTV surveillance. Coaches have a key role, but shortcomings in their approach need to be addressed. Exploitation by regular children of catch-up children is an important issue. Leadership changes can create uncertainty. Three forms of discipline are in place, but ineffective job desk implementation and changing rules challenge discipline. In conclusion, UPTD Kampung Anak Negeri plays a major role in controlling children’s behavior, but challenges and weaknesses need to be addressed to improve its effectiveness. Keywords: Street Children, Total Institutions, UPTD Kampung Anak Negeri. Pemberdayaan anak jalanan di Surabaya melalui Dinas Sosial Kota Surabaya membuat institusi penampungan anak bermasalah sosial yaitu UPTD Kampung Anak Negeri. Anak jalanan dibina untuk meningkatkan potensi, mengubah citra diri mereka menjadi normatif, dan mandiri. Membahas kehidupan dibalik UPTD Kampung Anak Negeri terdapat perilaku yang ditentukan institusi. Anak jalanan mengenal institusi dan menunjukkan tindakan yang sesuai dengan dan menentang aturannya. Penelitian ini menggunakan pendekatan kualitatif dengan perspektif Teori Total Institution Erving Goffman untuk menganalisis data. Hasil penelitian menunjukkan bahwa UPTD Kampung Anak Negeri berpengaruh besar terhadap anak-anak binaan. Faktor keluarga yang tidak harmonis memicu masuknya anak-anak ke lembaga ini. Di dalamnya, kontrol sosial ketat tercipta melalui aturan dan hukuman, membentuk perilaku anak-anak. Identitas mereka diubah menjadi "narapidana," menyebabkan kehilangan hak otonomi dan stigmatisasi. Konflik interpersonal antar staf menciptakan ketegangan sosial, dan perilaku anak-anak dipengaruhi oleh kontrol sosial, jadwal ketat, dan pengawasan CCTV. Pembina memiliki peran kunci, tapi kekurangan dalam pendekatan mereka perlu diatasi. Eksploitasi oleh anak reguler terhadap anak kejar paket menjadi isu penting. Perubahan kepemimpinan dapat menciptakan ketidakpastian. Tiga bentuk pendisiplinan diterapkan, tapi implementasi job desk yang tidak efektif dan aturan yang berubah-ubah menantang kedisiplinan. Kesimpulannya, UPTD Kampung Anak Negeri berperan besar dalam mengendalikan perilaku anak-anak, namun tantangan dan kelemahan perlu diatasi untuk meningkatkan efektivitasnya. Kata Kunci: Anak Jalanan, Institusi Total, UPTD Kampung Anak Negeri.